Correlation between socio-cognitive factors and intention to engage in premarital sex among late adolescents in Kuantan government secondary schools - Nurul Akmanidar binti Zainuddin
The consequences of adolescents in early involvement with sexual activity include sexually transmitted diseases, unwanted pregnancy, and unsafe abortion. Thus, this study aims to identify the socio-demographic and socio-cognitive factors (permissive attitude, social norms, and self-efficacy) associated with intention to engage in premarital sex among school-going late adolescent in Kuantan, Pahang. This cross-sectional study was conducted among students aged 18 to 19 years-old from nine government secondary schools in Kuantan district between March-June 2018. A total of 466 unmarried students responded to this topic using a self-administered validated Youth Sexual Intention Questionnaire (YSI-Q). Statistical analyses were done using IBM SPSS version 22.0. The results showed most of the participants were females (64.4%), Muslims (68.2%) and Malays (67.4%). Prevalence of premarital sex among school-going late adolescent was 1.5% predominantly by males (85.7%). Simple logistic regression on socio-cognitive factors showed for every one-unit increase in permissive attitude, social norms and self-efficacy scores, there were 1.424, 1.303 and 1.215 times increase the risk of having sexual intention, with the p-values and 95%CI of OR of 0.001, 1.268-1.600; 0.001, 1.191-1.425 and 0.001, 1.066-1.386, respectively. In the multivariate logistic regression, again being female was identified as having a lower risk to have sexual intention compared to male (p=0.001, OR=0.168, CI: 0.058-0.462).In contrary, non-Malay students had a higher risk compared to Malay students and ever smoke students had higher risk as compared to non-smoker students towards having sexual intention (p=0.001, OR=5.110, CI: 1.881-13.886 and p=0.019, OR=3.288, CI: 1.218- 8.875, respectively). Lastly, for each one-unit increase in permissive attitude score, there were 1.236 times increase risk of having sexual intention (p=0.002, OR=1.236, CI:1.084-1.410). In conclusion, the risk of having sexual intention was found to be higher among males, non-Malay students as well as higher among ex-smoker compared to non-smoker students and among those with higher permissive attitude scores. Therefore, further study and peer education intervention programs are needed for school-going adolescents, especially among male students to improve their attitude and prevent risky behavior.